Study of the Stability of a Viscous Solution of Naftifin Hydrochloride with a Combination of Polyethylene Glycols for External Use - S. I. Kosenkova; I. I. Krasnyuk; I. I. Krasnyuk (jr.); A. V. Belyatskaya; O. I. Stepanova; E. V. Mazyarkin; T. V. Korochkina; Yu. Ya. Kharitonov (Разработка и регистрация лекарственных средств)
Introduction. An innovative antifungal viscous solution based on naftifine hydrochloride with a combination of polyethylene glycols (PEG) was developed in the laboratory of Sechenov University. The developed preparation intended for external use. The active ingredient – naftifine hydrochloride has a wide spectrum of action against fungi cause onychomycosis. The polyethylene glycols are included in the developed dosage form of provide the necessary viscosity of the solution (for accurate application and retention in the field of application). The paper presents the results of a study of the stability of a viscous solution of naftifine hydrochloride with a combination of PEG for external use. Over the entire shelf life, the drug must retain the full its chemical, physical, biopharmaceutical and pharmacological properties.Aim. Determination of stability and expiration date of the shelf life of the developed solution of naftifine hydrochloride for external use, intended for the treatment of mycosis of the nail.Materials and methods. Naftifine hydrochloride solution, «Millipor» filter, UV spectrophotometry, potentiometry pH, capillary viscometry.Results and discussion. In the course of the study, the shelf life of the developed alcohol solution of naftifin hydrochloride with a combination of PEG was experimentally determined. The stability of the dosage form was determined by accelerated aging at a temperature of 40 ± 2 °C, in vivo at a temperature of no higher than 25 °C; and in a refrigerator at a temperature of 8 ± 2 °C. Assessment of the stability of the alcohol solution of naftifine hydrochloride was carried out according to the following indicators: the volume of the contents of the bottle, appearance, pH, quantitative content of the active substance, viscosity.Conclusion. Based on the studies, it is recommended to store the naftifine hydrochloride solution at room temperature not higher than 25 °C, in a dark place. It is also allowed to store the solution of naftifine hydrochloride in a refrigerator at a temperature of 8 ± 2 °C.